Lead-free ternary perovskite compounds with large electromechanical strains - Jarupoom P. (2014)
Lead-free compounds based on perovskite solid solutions in the ternary system (Bi1/2Na1/2)TiO3-(Bi1/2K 1/2)TiO3-Bi(X1/2Ti1/2)O 3, where X Ni and Mg have been shown to exhibit large electromechanical strains. While the perovskite end members Bi(Mg 1/2Ti1/2)O3 and Bi(Ni1/2Ti 1/2)O3 display limited stability in their pure state, both compounds were found to have solid solubilities of at least 50 mol. with (Bi1/2Na1/2)TiO3 and (Bi1/2K 1/2)TiO3. Most importantly, under relatively large applied fields, these materials exhibited large hysteretic electromechanical strains characterized by a parabolic shape. With effective piezoelectric coefficients (d33) greater than 500 pm/V, these systems have excellent potential as a Pb-free piezoelectric materials. © 2011 American Institute of Physics.